Hubungan Asupan Air, Status Hidrasi, Dan Kebugaran Remaja Di Pengungsian Petobo Kota Palu - Hardianti .; Sabaria Manti; Burhanuddin Bahar; Nurhaedar Jafar; Marini Amalia Mansur (Departement of Nutrition, Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Introduction: Disasters experienced by citizen in Palu forced the community moved to refuge camp. The movement makes the community live in a place with limited clothe food, shelter, and clean water. physical fitness in adolescents is low and forgotten. Based on conditions, the problem found is the relationship of Water Intake, Hydration Status and Adolescent fitness in the Petobo refugee camp. Purposes: To find out the relationship between water intake, hydration status, and the level of adolescent fitness in the Petobo refugee camp. Material and Methods: Research using analytic observational methods using cross sectional design. The sample are 59 youth in Petobo refugee, using the Total Sampling Method. Fitness status is taken through Balke Test, Water Intake is collected based on Recall Results, and Hydration status data is analyzed using the urine color analysis method. Results: The results found that adolescents in refugee petobo with less than 47% Fitness Status, while less by 41% and enough by 12%, Adolescent Water Intake with a category of less than 69%, quite 17%, and more by 14%. Hydration status of adolescents with severe dehydration category 39%, dehydration 27%, and well hydrated 34%. In this study, the results obtained based on the Chi-square test that there is a relationship between water intake and fitness level with p value 0.001 <0.05, and there is a relationship between Hydration Status and fitness level with p value 0.025 <0.05. Conclusion: There is a relationship between water intake, hydration status and the level of adolescent fitness in Petobo refugee camps.